2019
DOI: 10.1163/15685411-00003209
|View full text |Cite
|
Sign up to set email alerts
|

My favourite nematode – Phasmarhabditis hermaphrodita

Abstract: SummaryThe terrestrial gastropod parasitic nematode Phasmarhabditis hermaphrodita is the only nematode that evolved to infect and kill slugs and snails. Because of this ability it has been formulated into a biological control agent for gardeners. In this Forum article, the author outlines several reasons why P. hemaphrodita is a nematode that is worth studying, including its ability to control the behaviour and kill slug hosts. The author discusses how P. hemaphrodita is being developed as a model nematode to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…More sophisticated genetic techniques have been shown to work in EPNs, such as RNAi in S. carpocapsae 238 and H. bacteriophora, 239 and even transgenic techniques in H. bacteriophora. 240 Although P. hermaphrodita has been proposed as a model nematode to understand the genetic mechanisms of parasitism, [241][242][243][244] development of techniques for genetic manipulation are in their infancy. 40 With the subsequent sequencing of the genome ongoing (Sheehy, Rae, unpublished data), the unravelling of the genetic blueprint of P. hermaphrodita may aid in the development of molecular tools.…”
Section: 1mentioning
confidence: 99%
“…More sophisticated genetic techniques have been shown to work in EPNs, such as RNAi in S. carpocapsae 238 and H. bacteriophora, 239 and even transgenic techniques in H. bacteriophora. 240 Although P. hermaphrodita has been proposed as a model nematode to understand the genetic mechanisms of parasitism, [241][242][243][244] development of techniques for genetic manipulation are in their infancy. 40 With the subsequent sequencing of the genome ongoing (Sheehy, Rae, unpublished data), the unravelling of the genetic blueprint of P. hermaphrodita may aid in the development of molecular tools.…”
Section: 1mentioning
confidence: 99%
“…and Heterorhabditis spp., at least if M. osloensis is included in the preparation. It has been suggested that P. hermaphrodita may be pathogenic to molluscs even in the absence of M. osloensis [ 161 , 162 ]. If that is so, preparations of P. hermaphrodita that do not include Moraxella or other associated bacteria would not raise the question of the applicability of FIFRA.…”
Section: Current Best Practices Sarcophagid Flies and Phasmarhabditismentioning
confidence: 99%